2014
DOI: 10.1016/j.chom.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Human Responses to Influenza Vaccination Show Seroconversion Signatures and Convergent Antibody Rearrangements

Abstract: Summary B cells produce a diverse antibody repertoire by undergoing gene rearrangements. Pathogen exposure induces the clonal expansion of B cells expressing antibodies that can bind the infectious agent. To assess human B cell responses to trivalent seasonal influenza and monovalent pandemic H1N1 vaccination, we sequenced gene rearrangements encoding the immunoglobulin heavy chain, a major determinant of epitope recognition. The magnitude of B cell clonal expansions correlates with an individual’s secreted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
238
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(263 citation statements)
references
References 28 publications
15
238
0
Order By: Relevance
“…An amino acid sequence dendrogram of the VDJ regions (Supplemental Figure 2) revealed the diversity in these sequences generated by V region somatic mutations (which induced an average of 7-amino acid changes per sequence) and clonal D-J combinations. This result is very similar to findings by Krause et al (28) and Jackson et al (29), who identified very similar sets of clones based on V H 3-7/ J H 6 rearrangements in individuals responding to the Sa site of H1N1pdm09 HA and discussed the evidence for intraclonal divergence and interclonal convergence of these sequences.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…An amino acid sequence dendrogram of the VDJ regions (Supplemental Figure 2) revealed the diversity in these sequences generated by V region somatic mutations (which induced an average of 7-amino acid changes per sequence) and clonal D-J combinations. This result is very similar to findings by Krause et al (28) and Jackson et al (29), who identified very similar sets of clones based on V H 3-7/ J H 6 rearrangements in individuals responding to the Sa site of H1N1pdm09 HA and discussed the evidence for intraclonal divergence and interclonal convergence of these sequences.…”
Section: Resultssupporting
confidence: 80%
“…The dominance of HA head-specific V H 3-7*01/J H 6*02 sequences that we found in the largest V H -related set has been seen in other individual responses following exposure to H1N1pdm09 (28,29). For example, the V H 3-7/J H 6 antibodies rearranged with a different group of 4 D segments (3-16*02, 3-22*01, 6-13*01, and 4-17*01) from those from our donor (3-16*01, 3-3*01 in reading frame 2 and 3, and 3-3*02) (28).…”
Section: Discussionmentioning
confidence: 65%
“…However, previous work was limited by small numbers of elderly individuals analyzed (8), did not analyze in detail the composition of the oligoclonal lineages (8), or did not study the effect of applying an immune stimulus such as a vaccine (10). Furthermore, previous B-cell repertoire studies have focused only on isolated aspects of B-cell mutation counts, V/D/J-gene use levels, lineage sizes, and convergent CDR3 sequences (8,(10)(11)(12)(13) without analyzing the character of mutations and without using the full phylogenetic information inherent in the IGH repertoire to quantify dissimilarities between immune systems.…”
mentioning
confidence: 99%
“…Previous studies have, for example: revealed the association of certain germline genotypes with susceptibility to such diseases as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and multiple sclerosis (MS) (5,6); found correlations of age with a reduced Ig clonal diversity and less intense response to immune challenge (7,8); found overly expanded clones in cases of lymphoma (9,10); and discovered convergent Ig evolution across subjects in response to certain immune challenges (11,12). These repertoire-sequencing (Rep-Seq) studies have benefitted from improvements in sequencing technologies, which allow for the generation of millions of reads per run (13).…”
mentioning
confidence: 99%